2019
DOI: 10.1016/j.ijheatmasstransfer.2018.09.079
|View full text |Cite
|
Sign up to set email alerts
|

Influence factors of the evaporation rate of a solar steam generation system: A numerical study

Abstract: Many efforts have been dedicated to improve the solar steam generation by using a bi-layer structure. In this paper, a two-dimensional mathematical model describing the water evaporation in a bi-layer structure is firstly established and then the finite element method is used to simulate the effects of different influence factors on the evaporation rate. Results turn out that: besides the high solar energy absorptivity of the first-layer, an optimum porosity of the second-layer porous material should be applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…The sample was irradiated by a solar simulator, and the temperature of the sample surface was recorded by an infrared camera. The solar steam performance of fibers was measured at the ambient temperature of ≈20 °C and a humidity condition of ≈12% . The weight change was monitored by electronic analytical balance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample was irradiated by a solar simulator, and the temperature of the sample surface was recorded by an infrared camera. The solar steam performance of fibers was measured at the ambient temperature of ≈20 °C and a humidity condition of ≈12% . The weight change was monitored by electronic analytical balance.…”
Section: Methodsmentioning
confidence: 99%
“…The solar steam performance of fibers was measured at the ambient temperature of %20 C and a humidity condition of %12%. [49] The weight change was monitored by electronic analytical balance. www.advancedsciencenews.com www.entechnol.de…”
Section: Methodsmentioning
confidence: 99%
“…[1,11,12] Of late, with a wide variety of new solar-absorber materials mushrooming, the solar desalination approach has begun to bear fruit. However, quite opposite to the common notion that the relative humidity (RH) affects ER, recent reports have confirmed that the solar evaporation is still able to maintain a high rate even when the RH greatly increases, [20,21] but understanding of how the evaporation can be sustained under such high humidity is still inadequate. [1,19] However, current studies often overlook the impacts from environment and the system itself.…”
mentioning
confidence: 86%
“…Those neglectful factors, such as humidity that broadly changes with place and time, may be capable of manipulating the solar evaporation process. However, quite opposite to the common notion that the relative humidity (RH) affects ER, recent reports have confirmed that the solar evaporation is still able to maintain a high rate even when the RH greatly increases, [20,21] but understanding of how the evaporation can be sustained under such high humidity is still inadequate. [22] It is therefore more pressing to systematically study how the various system/ambient factors influence the evaporation process than to engineer a new solar absorber material, which sums up the motive of this work.This work shines light on the roles of relative humidity level of the ambience/system, waterlogged surface level, specific weight, carbonization thickness, and water salinity in influencing the water evaporation in a solar steam generation system, where microchanneled balsa wood was employed as an ideal research model for quantitative comparisons.…”
mentioning
confidence: 97%
“…50,51 Finally, the thermal insulation design in the improved system could almost limit all heat on the evaporation surface and thereby importantly reduce the heat losses. 52 Therefore, a relatively high evaporation efficiency has been achieved in this work.…”
Section: Effects Of the Thermal Insulationmentioning
confidence: 99%